Kebutuhan untuk Mengatasi Kecemasan pada Mahasiswa Baru Program Studi Akuntansi dengan Latar Belakang yang Berbeda: Suatu Penelitian Eksperimen-Kuasi - Sondakh, Antonius Grivaldi (CV. Kalimasada Group, 2024)
New students from SMU-IPA often worry about their ability to compete with peers from SMU-IPS and SMK-Accounting. This study employs a quasi-experimental method to address these concerns by extending previous findings on the relationship between school background and understanding of basic accounting. Introductory accounting education in the first year serves as the experimental manipulation. The experimental group consists of third-semester students, while the control group comprises first-semester students. Using prospect theory, this study reveals that the initial concerns of SMU-IPA students become unfounded after receiving basic accounting instruction. The findings of this research are beneficial for accounting programs to reassure prospective students and their parents about choosing accounting as a study option.